Death, Freedom, Isolation and Meaninglessness and the Existential Psychotherapy of Irvin D. Yalom - Berry-Smith, Stephen Frederick (Auckland University of Technology, 2012)
This dissertation examines the work of existential psychotherapist Irvin D. Yalom. Yalom is acknowledged and respected globally for his contributions to contemporary psychotherapy; both for his theoretical understanding and his stance for practice which posits that a genuine, transparent, human connection in the therapeutic encounter is one that provides the most beneficial environment for emotional healing. His theory and approach to practice is grounded in the understanding that all human beings face four ultimate existential concerns – death, freedom, isolation and meaningless. Furthermore, he is of the profound belief that all psychopathologies are derivatives of the anxieties generated from awareness of the four concerns, and that a vital task of human development is to confront, and come to terms with the realities that each concern presents. This dissertation adopts the methodology of a traditional literature review to examine Yalom’s books, essays and interviews, and provides a synthesised study of his theory of Existential Psychotherapy and the implicit meaning of the four ultimate concerns. Included are critiques and comments from other contributors. A further aspect of the dissertation draws attention to some of the contrasting opinions that exist between psychoanalytic psychotherapy and those of Yalom’s existential approach. Lessons for practice are summarised and suggestions for future research are offered.
Keywords: Yalom; Existential; Irvin; Psychotherapy